FACTORS AFFECTING THE ATTITUDES OF VIETNAMESE RURAL YOUTH (BUYERS) ON E-COMMERCE PLATFORMS - AN EMPIRICAL STUDY IN RURAL AREAS OF HANOI - Xuan Phuc, Tran; Nho Quyet, Tran (Journal of Forestry Science and Technology, 2022)
This study examines factors affecting the attitude of Vietnamese rural youth in the e-commerce market, and how attitude influences the intention to shop online. The authors propose a research model consisting of 6 factors, namely perceived usefulness, perceived ease of use, compatibility, risk, subjective behavioral controlandperceived behavioral control. Due to the outbreak of Covid-19, sample data were collected through an online survey from December 2021 to February 2022, with 352 questionnaires collected from rural youth who are online shoppers (aged 18 to 40 years old) living in Hanoi. After the removal of invalid responses, 304 valid questionnaires were selected for analysis. Structural equation modeling (SEM) was applied to estimate the impact of six factors on consumers' attitudes. Findings: Online shopping attitude of rural youth is positively affected by perceived behavioral control, perceived usefulness, perceived ease of use, compatibility and subjective behavior control. The effect of compatibility, however, is not statistically significant. Risk has a negative effect on attitude, although this is not statistically significant. It is noteworthy that the six variables included in the hypothetical model explain nearly 50% of the change in online shopping attitudes of rural youth. In addition, a positive attitude can play a critical role in boosting online shopping intention of rural youth.